Environ-economic balance analysis in bilateral industrial trade: a comparison between Australia and China - Gao, Qun; Liu, Bin; Li, Junjie; Liu, Chunlu; Xu, Youquan (Technological and Economic Development of Economy, 2022)
Exchanges of products and services in bilateral industries may be accompanied by environmental and economic inequalities which lead to imbalanced situations in relation to environmental protection and economic development. In a close trade relationship between two countries such as Australia and China, their industries inevitably affect each other. This study maps the embodied CO2 emissions and value added in bilateral trade under the input–output model and measures the unequal exchanges in such trade using an originally established industrial environ-economic balance index. The bilateral trade between Australia and China is taken as an example to validate the outcomes of the research method. The results indicate that in 2014, Australia transferred 580.90 billion tons of CO2 and 105.85 billion USD of value added to China, while approximately 375.65 billion tons of CO2 and 25.15 billion USD of value added flowed from China to Australia. China’s manufacturing, construction, and services and other industries, and China’s and Australia’s real estate activities industries had net inflows of embodied CO2 emissions and value added, indicating these industries paid economic costs in return for reducing environmental pressure. In inter-industrial trade between Australia and China, 49 pairs of bilateral industrial trades were relatively fairly balanced, while the remaining 15 pairs of inter-industrial trades were imbalanced. The established environ-economic balance analysis method and quantitative findings are valuable for better understanding the environment impacts of the economic development of national economies and developing national policies in corresponding to the rising environmental issues.